2007
DOI: 10.1007/s10633-006-9038-5
|View full text |Cite
|
Sign up to set email alerts
|

Hypobaric hypoxia reduces the amplitude of oscillatory potentials in the human ERG

Abstract: These results appear to support the notion that the inner layers of the retina presumed to be the main source of the OPs, display the highest sensitivity towards circulatory and/or hypoxic challenges.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
2
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 27 publications
5
28
2
3
Order By: Relevance
“…In addition, the reduction in the V max , as determined by the Naka-Rushton analysis of the b-wave, may be attributed to a reduced function in the inner retina. This is in line with previous results demonstrating a reduction of the inner retinal thickness in OIR rodents (Downie et al 2007(Downie et al , 2010Fulton et al 1999;Vessey et al 2011) and confirms the notion that the inner layers of the retina display the highest sensitivity towards circulatory and/or hypoxic challenges (Janaky et al 2007).…”
Section: Electroretinographic Responses and Hypoxia Effectssupporting
confidence: 92%
“…In addition, the reduction in the V max , as determined by the Naka-Rushton analysis of the b-wave, may be attributed to a reduced function in the inner retina. This is in line with previous results demonstrating a reduction of the inner retinal thickness in OIR rodents (Downie et al 2007(Downie et al , 2010Fulton et al 1999;Vessey et al 2011) and confirms the notion that the inner layers of the retina display the highest sensitivity towards circulatory and/or hypoxic challenges (Janaky et al 2007).…”
Section: Electroretinographic Responses and Hypoxia Effectssupporting
confidence: 92%
“…9 -11 Comparable observations have been made on humans during high altitude or simulated hypobaric hypoxia. [12][13][14] In our previous study, we further demonstrated an unequal eccentric distribution of the electroretinographic response to acute hypoxia. 8 Sudden physiological perturbations tend to elicit not only acute but also chronic responses, often of a counterregulatory nature.…”
mentioning
confidence: 61%
“…The first factor is usually caused by GB, hypotension, atherosclerosis, diabetes, occlusive diseases of the large blood vessels, blood diseases. From local changes are the most important vessels atheromatosis, violations of the vascular endothelium [16,17,18,19].…”
Section: Discussionmentioning
confidence: 99%